Composite Face Effect Predicts Configural Encoding in Visual Short-Term Memory - Azer, Lilian; Zhang, Weiwei (Frontiers in Psychology, 2019)
In natural vision, visual scenes consist of individual items (e.g., trees) and global properties of items as a whole (e.g., forest). These different levels of representations can all contribute to perception, natural scene understanding, sensory memory, working memory, and long-term memory. Despite these various hierarchical representations across perception and cognition, the nature of the global representations has received considerably less attention in empirical research on working memory than item representations. The present study aimed to understand the perceptual root of the configural information retained in Visual Short-term Memory (VSTM). Specifically, we assessed whether configural VSTM was related to holistic face processing across participants using an individual differences approach. Configural versus item encoding in VSTM was assessed using Xie and Zhang’s (2017) dual-trace Signal Detection Theory model in a change detection task for orientation. Configural face processing was assessed using Le Grand composite face effect (CFE). In addition, overall face recognition was assessed using Glasgow Face Matching Test (GFMT). Across participants, holistic face encoding, but not face recognition accuracy, predicted configural information, but not item information, retained in VSTM. Together these findings suggest that configural encoding in VSTM may have a perceptual root.